The Influence of Benjamin Graham Selection Criteria On Stock Return: The Influence of Benjamin Graham Selection Criteria On Stock Return - Devika Cherly Putrihadiningrum; Cynthia Eka Violita (TALI JAGAD JOURNAL, 2023)
Value investing strategies date back to the studies of Benjamin Graham and David Dodd (1934), premised on the idea of investing into undervalued but profitable shares. In this Article, The purpose of this study will be to measure the effect of Devident Yield on Stock Return using Graham Criteria. There are 14 valiable Stock from 2012-2020 that passed with Benjamin Graham selection criteria. The result of the research by Using Benjamin Graham selection criteria to selected value invesment Dividend yield don’t have significant effect on stock return. Keyword : Dividend Yield, Stock Return, Graham Criteria